Rare-Earth Free Unity Power Factor Bi-Axial Excitation Synchronous Machine for Traction Applications - Chattopadhyay, Ritvik; Jung, Junyeong; Islam, Md. Sariful; Boldea, Ion; Husain, Iqbal (IEEE transactions on industry applications, 2024)
Rare-earth-based traction machines are subject to supply chain, geo-political, and price fluctuation issues, which makes rare-earth-free motor topologies attractive for electric vehicle (EV) traction applications. In this research, a 24-slot/4-pole, unity power factor, air-cooled, rare-earth-free bi-axial excitation synchronous machine (BESM) with ferrite magnets is explored for traction applications. The proposed machine achieves a unity power factor due to the presence of stator flux countering magnets embedded in the rotor, while the torque-producing component of the rotor flux is produced by DC field windings. A 4.2 kW, 40 Nm BESM is designed using a 2D-finite element analysis (FEA) based optimization, and a prototype is fabricated. The performance of the prototype is experimentally verified up to the rated torque in a dynamometer test setup. Based on the experimental validation of the prototype, a scaled-up 100 kW BESM is designed and characterized using FEA to verify the effectiveness of the proposed concept for high-power traction applications.